1988
DOI: 10.1017/s0043174500075032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environment and Adjuvants on Asulam Phytotoxicity

Abstract: Experiments were conducted to determine the influence of various factors on asulam {methyl[(4-aminophenyl)sulfonyl] carbamate} toxicity to flax (Linum usitatissimumL.) and wild oats (Avena fatuaL. # AVEFA). Asulam toxicity to both flax and wild oats generally increased as temperature, humidity, and soil moisture increased after treatment. Octoxynol {α-[p-1,1,3,3-tetramethyl butyl phenyl]-ω-hydroxypoly(oxyethylene)} in the spray solution increased asulam toxicity to both species in all environments. Octoxynol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…In the second study in 1992 the critical rainfree period was 14 HAT. The level of johnsongrass control observed after the critical rainfree period in the second study was equivalent to that observed and/or taller (3,13). In study 3 in 1993, even though johnsongrass plants were shorter, the rhizome system was i5of-\ \ \ more extensive because the site was a year older, being established at the same time as the 1992 studies.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…In the second study in 1992 the critical rainfree period was 14 HAT. The level of johnsongrass control observed after the critical rainfree period in the second study was equivalent to that observed and/or taller (3,13). In study 3 in 1993, even though johnsongrass plants were shorter, the rhizome system was i5of-\ \ \ more extensive because the site was a year older, being established at the same time as the 1992 studies.…”
Section: Resultssupporting
confidence: 58%
“…Surfactants are commonly used to enhance herbicide activity and to increase leaf absorption (9,10,11,13). Under adverse environmental conditions, enhancement of herbicide absorption increased johnsongrass control (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of temperature on herbicide translocation and phytotoxicity varied (Blair et al 1983, Coupland 1986, Devine et al 1983, Grafstorm and Nalewaja 1988, Kells et al 1984, Klevorn and Wyse 1984, Morrison 1983, Nalewaja and Woznica 1988, Smeda and Putnam 1990, Wills 1984, Wills and McWhorter 1983. There have been limited studies on the effects of light intensity on herbicide performance and underlying physiologic processes.…”
mentioning
confidence: 99%
“…The amount of asulam available for translocation to the above-and below-ground meristematic regions of rhi zome johnsongrass depends upon the amount of asulam absorbed. Absorption can be limited by factors such as the plant's metabolic activity, insufficient leaf wetting, wash-off of chemical from rainfall, or temperature or moisture stress (3,5,9,13). When absorption is reduced, the absorbed asulam is probably diluted to the point that toxic levels can accumulate only in the most dominant buds of the shoot and rhizome thereby reduc ing the degree and longevity of control.…”
Section: Introductionmentioning
confidence: 99%